(untitled) (Siddhajyoti Interdisciplinary Journal, 2026)
This study looks at the elderly population of Nepal and its gender and regional differences that are the results of the demographic transition between the years 1991 and 2021. It examines the changes in the population structure of the country using the data of the national census and descriptive statistics analysis, and how the age composition has changed the population structure. According to the findings, the proportion of the population that is 60 years of age or older increased steadily from 5.8% in 1991 to 10.2% in 2021. The population has undergone minor but significant changes. It can be seen that there are regional inequalities, a more aged population in the Gandaki and Koshi Provinces than there is in Madhesh and Karnali. The aged also show a high prevalence of women over men, and this explains the importance of gender ageing policies. The paper emphasises that population ageing has both negative health, employment, and social protection issues, but also covers the way to inclusive and sustainable development in case it is properly managed. Such implications include the necessity of including ageing issues in education, welfare, and the labor system, and interventions that are consistent with regional and gender demands. This study helps the planners and policy-makers of Nepal in formulating evidence-based information about the ageing processes by filling the gaps in the existing empirical data regarding the topic to facilitate optimal promotion of equitable, healthy, and environmentally friendly population policies.